2018
DOI: 10.1371/journal.pgen.1007846
|View full text |Cite
|
Sign up to set email alerts
|

β-actin regulates a heterochromatin landscape essential for optimal induction of neuronal programs during direct reprograming

Abstract: During neuronal development, β-actin serves an important role in growth cone mediated axon guidance. Consistent with this notion, in vivo ablation of the β-actin gene leads to abnormalities in the nervous system. However, whether β-actin is involved in the regulation of neuronal gene programs is not known. In this study, we directly reprogramed β-actin+/+ WT, β-actin+/- HET and β-actin-/- KO mouse embryonic fibroblast (MEFs) into chemically induced neurons (CiNeurons). Using RNA-seq analysis, we profiled the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…A potential relationship between β-actin and BAF/PRC mediated chromatin remodeling raises the possibility that nuclear β-actin levels may play a regulatory role in shaping the chromatin landscape during development. Such a function is consistent with the wellestablished roles of actin in transcriptional reprogramming (16) and our previous work showing that βactin knockout cells exhibit specific defects in gene regulation during neural reprogramming (7). We therefore hypothesize that regulation of nuclear β-actin levels may potentially influence both local chromatin accessibility and higher-order genome organization.…”
Section: Introductionsupporting
confidence: 90%
“…A potential relationship between β-actin and BAF/PRC mediated chromatin remodeling raises the possibility that nuclear β-actin levels may play a regulatory role in shaping the chromatin landscape during development. Such a function is consistent with the wellestablished roles of actin in transcriptional reprogramming (16) and our previous work showing that βactin knockout cells exhibit specific defects in gene regulation during neural reprogramming (7). We therefore hypothesize that regulation of nuclear β-actin levels may potentially influence both local chromatin accessibility and higher-order genome organization.…”
Section: Introductionsupporting
confidence: 90%
“…Recent work has shown that the nuclear β-actin pool significantly contributes to neuronal development by regulating genome organization and activation of neuronal programs during neurogenesis. To address this question, we directly reprogrammed wild-type and β-actin knockout embryonic fibroblasts as well as embryonic fibroblasts from a heterozygous mouse where only one of the βactin alleles was disrupted [17]. Compromising βactin levels was associated with impaired expression of neural and proneural genes involved in the neuronal cytoskeleton, synapse, axon development and guidance, voltage-gated ion channels and neuronrelated transcription factors.…”
Section: Neurogenesis As a Paradigm To Study The Role Of Actin In Genmentioning
confidence: 99%
“…Compromising βactin levels was associated with impaired expression of neural and proneural genes involved in the neuronal cytoskeleton, synapse, axon development and guidance, voltage-gated ion channels and neuronrelated transcription factors. Notably, members of the Zic and Irx family of genes, which are involved in the onset of neuronal fate [93], were severely down-regulated in the absence of β-actin [17]. The overall impaired induction of neuronal genes in βactin knockouts was correlated with increased H3K9Me3 levels and loss of Brg1 (ATPase subunit of BAF chromatin remodeling complex) occupancy at transcription start sites of multiple gene loci, including Zic and Irx genes.…”
Section: Neurogenesis As a Paradigm To Study The Role Of Actin In Genmentioning
confidence: 99%
See 2 more Smart Citations